Edukasi Jemaat Dalam Menghadapi Covid Di GKSI Betlehem Jemaat Grogol Permai - Alexius Adam; Octaversya Krisanta Rendi Ratag; Hariyanto Hariyanto (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2022)
This study aims to determine the education of the congregation in dealing with Covid at GKSI Bethlehem, Grogol Permai Congregation. The population in this study was the GKSI Bethlehem Satellite Grogol Permai congregation who were considered to be adults (20+) and over, which amounted to 258 of the entire congregation. Sampling used a random sampling technique, namely random sampling with the slovin formula, then found a sample of 86 congregation members. The instrument used to collect research data using a Likert scale model questionnaire. Data processing uses program modules with percentages. The results of data analysis stated that the variable categories and overall aspects were good. The results of the hypothesis test have a positive and significant effect, which strengthens H1 is accepted. Based on the research paradigm, it is explained that Church Education has an impact of 45.9% on the attitude of the congregation. Age background, educational status, economy, and length of time in church also affect the attitude of the congregation in dealing with the COVID-19 pandemic.